AUTOMATION OF METROLOGICAL MAINTENANCE AT THE ENTERPRISES - I.G. KOSHLYAKOVA; E.V. PEYEVA; K.O. SUVOROVA; E.A. KOSHLYAKOVA (Advanced Engineering Research)
Solution of the problem of acceleration and increase of measurement tools choice objectivity with help of database creation on ACCESS basis is considered. As a result the opportunity of a wide review of measurement tools of the set measured size, their choice according to the required metrological and technical characteristics, and getting full information on the chosen measurement tools is provided. The developed database can be used also for the registration of  measurement tools,  the control time sig-nalling and for other actions with measurements and test equipment at the enterprises.